Detection of recurring vulnerabilities in computing services. (19th May 2022) - Kumar, Sarvesh; Dubey, Kamlesh Kumar; Gautam, Arun Kumar; Verma, Shikha; Kumar, Vinay; Mamodiya, Udit
Abstract: In real time the open-source formulation and their effects are becoming highly enhanced for the development of applications. Security is the major area of technology to detect vulnerabilities. Mutual detection is time taking and very tough which is not feasible. There are a lot of techniques for the detection of vulnerabilities. In this research work we have developed the hybrid approach for the detection. We are using a huge software system. Our approach is based on the token formulation and fingerprint-based detection of errors. The tool we are designing is able to detect and patch the security related threats. We have also compared our approach with the existing approach and the performance and efficiency of our tool is much better than others.